Design and Fabrication of a Parallel Mechanism for Foot/Ankle Rehabilitation Therapy - Krishnan, S. (Springer, 2020)
This paper presents the development of a low-cost and mobile parallel manipulator for treatment of ankle sprain rehabilitation. The manipulator is called Ankle Rehab Robot (ARR) which has bio-inspired design devised after careful studies of improvement opportunities in the existing ankle rehabilitation devices. Ankle Rehab Robot employs lightweight but powerful pneumatic muscle actuators (PMA) which imitates skeletal muscle in actuation. Some of the key existing sprained ankle rehab robots/prototypes (Intermediate Complexity Devices) was carefully studied and reviewed in order to find the limitations or improvement opportunities. The research approach has been conversed in brief and the ARR design has been described and analysed. Actuator and prototype testing were conducted to obtain specification data of the proposed Ankle Rehab Robot (ARR). For evaluation of mobility and economics, some of the data collected were used for comparison between some of the key (reviewed) existing ankle rehabilitation devices and the ARR Manipulator. From the results attained, target of the research was successfully met. Future works and refinements have been discoursed to improvise the existing Ankle Rehab Robot (ARR). Â© 2020, Springer Nature Singapore Pte Ltd.